The Decision to Invest in Child Quality over Quantity : Household Size and Household Investment in Education in Vietnam - Dang, Hai-Anh; Rogers, F. Halsey (World Bank, Washington, DC, 2013)
During Vietnam's two decades of rapid economic growth, its fertility rate has fallen sharply at the same time that its educational attainment has risen rapidly -- macro trends that are consistent with the hypothesis of a quantity-quality tradeoff in child-rearing. This paper investigates whether the micro-level evidence supports the hypothesis that Vietnamese parents are in fact making a tradeoff between quantity and quality of children. The paper presents new measures of household investment in private tutoring, together with traditional measures of household investments in education. It analyzes data from the Vietnam Household Living Standards Surveys and instruments for family size using the distance to the nearest family planning center. The estimation results show that families do indeed invest less in the education of school-age children who have larger numbers of siblings. This effect holds for several indicators of educational investment -- including general education expenditure and various measures of private tutoring investment -- and is robust to various definitions of family size and model specifications that control for community characteristics as well as the distance to the city center. Finally, the results suggest that tutoring may be a better measure of quality-oriented household investments in education than traditional measures like enrollment, which are arguably less nuanced and household-driven.